Unsteady MHD Casson fluid flow in a vertical cylinder with porosity and slip velocity effects / Wan Faezah Wan Azmi ... [et al.] - Wan Azmi, Wan Faezah; Mohamad, Ahmad Qushairi; Lim, Yeou Jiann; Shafie, Sharidan (2021)
The significance of Casson fluid flow in the cylinder has recently attracted many researchers to study analytically, numerically and experimentally due to its unique behavior and relation with the reallife applications such as blood flow in vessel tubes. Due to the lack of consideration for slip boundary conditions, this paper investigated analytically the effects of slip velocity and magnetic on the pulsatile flow of Casson fluid past through a vertical cylinder in a porous medium. The Casson fluid model was used under the influences of a uniformly distributed magnetic field, oscillating pressure gradient and porous medium in order to obtain governing equations. The analytical solutions of velocities were then solved by Laplace and finite Hankel transforms. These fluid velocities were then presented graphically. The result shows the slip velocity influenced the behavior of the Casson parameter and fluid velocity. Besides that, fluid velocity increases with the increase of Darcy number, while it decreases when the magnetic parameter increases. Thus, these findings are beneficial to explore further in the applications of biomedical engineering and pathology.